Managerial tactics for communicating negative performance feedback. Issue 5 (1st August 2016) - Brown, Michelle; Kulik, Carol T.; Lim, Victoria
Abstract : Purpose: – Delivering negative feedback to employees is highly problematic for managers. Negative feedback is important in generating improvements in employee performance, but likely to generate adverse employee reactions. However, if managers do not address poor performance, good performers may become demoralized or exit the organization. The purpose of this paper is to investigate how managers communicate negative feedback and the factors that drive their choice of tactic. Design/methodology/approach: – The authors use interview data from practicing line managers with experience in delivering negative feedback to learn whether their tactic choices are consistent with Implicit ("best practice") or Contingency ("best fit") theory. Findings: – The authors identify five negative feedback tactics: evidence, emotive and communication tactics are foundation tactics while evidence + communication and evidence + emotive tactics are bundles of the foundation tactics. Managers apply a "best fit" approach from a set of "best practice" negative feedback options. The choice of negative feedback tactic is driven by the manager's assessment of the "best fit" with the employee's personality. Research limitations/implications: – Most of the managers believed that their negative feedback tactic had been effective. Future researchers should investigate which negative feedback tactics employees regard as most effective. Practical implications: – A best fit approach to the delivery of negative feedback requires organizations to give managers discretion in the delivery of negative feedback. Managers may mis-assess fit which can undermine the effectiveness of the appraisal process. Originality/value: – The authors focus on how negative feedback is communicated by managers. Existing research focusses on reactions to negative feedback without taking into account how it is delivered.